Cassava haplotype map highlights fixation of deleterious mutations during clonal propagation - Ramu, P.; Esuma, W.; Kawuki, R.S.; Rabbi, Ismail Y.; Egesi, Chiedozie N.; Bredeson, J.V.; Bart, R.S.; Verma, J.; Buckler, E.S.; Lu, F (Springer, 2017)
Cassava (Manihot esculenta Crantz) is an important staple food crop in Africa and South America; however, ubiquitous deleterious mutations may severely decrease its fitness. To evaluate these deleterious mutations, we constructed a cassava haplotype map through deep sequencing 241 diverse accessions and identified >28 million segregating variants. We found that (i) although domestication has modified starch and ketone metabolism pathways to allow for human consumption, the concomitant bottleneck and clonal propagation have resulted in a large proportion of fixed deleterious amino acid changes, increased the number of deleterious alleles by 26%, and shifted the mutational burden toward common variants; (ii) deleterious mutations have been ineffectively purged, owing to limited recombination in the cassava genome; (iii) recent breeding efforts have maintained yield by masking the most damaging recessive mutations in the heterozygous state but have been unable to purge the mutation burden; such purging should be a key target in future cassava breeding.